2009
DOI: 10.1002/chem.200801589
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenyl‐Ended Thieno–Vinylene Oligomers: Donor–Acceptor Polarization and Mixed‐Valence Properties with Emphasis on the Raman Mapping of Localized‐to‐Delocalized Transitions

Abstract: What's your role? New oligothiophene-vinylene compounds have been synthesized to study the role of the conjugated chain in two different cases (see scheme; MV=mixed valence). The electronic and molecular structures were analyzed by means of electronic, X-ray photoelectron, and Raman spectroscopy, together with thermo spectroscopy, electrochemistry, and DFT calculations.New oligothiophene-vinylene compounds have been synthesized in order to study the role of the conjugated chain in two different cases: 1) when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 84 publications
0
5
1
Order By: Relevance
“…For 3 EDOT, only two stable oxidation potentials were measured, [12] which appear at higher potentials than the ones for 3 EDOTV, which is in line with the greater p space of the later imparted by the intercalation of vinylene bonds (see DE values in Table 2). For 4 TV, [5,17] the DE value between the dicationic and the cationic oxidation potentials was measured to be 0.2 V, which is larger than 0.17 V, which was measured for our 4 EDOTV sample, revealing the stabilising effect of the EDO groups for the oxidised species. There is a good linear fit of the first two oxidation potentials with the reciprocal of the chain length (see Figure S25 in the Supporting Information) for the three n EDOTV compounds indicating that the major role in the stabilisation of the positive charge is imparted by the conjugated C=C/CÀC bond sequence.…”
Section: Electrochemical Propertiescontrasting
confidence: 58%
“…For 3 EDOT, only two stable oxidation potentials were measured, [12] which appear at higher potentials than the ones for 3 EDOTV, which is in line with the greater p space of the later imparted by the intercalation of vinylene bonds (see DE values in Table 2). For 4 TV, [5,17] the DE value between the dicationic and the cationic oxidation potentials was measured to be 0.2 V, which is larger than 0.17 V, which was measured for our 4 EDOTV sample, revealing the stabilising effect of the EDO groups for the oxidised species. There is a good linear fit of the first two oxidation potentials with the reciprocal of the chain length (see Figure S25 in the Supporting Information) for the three n EDOTV compounds indicating that the major role in the stabilisation of the positive charge is imparted by the conjugated C=C/CÀC bond sequence.…”
Section: Electrochemical Propertiescontrasting
confidence: 58%
“…This work presents the preparation of a series of medium to large size oligothiophene-vinylene oligomers (Scheme and Supporting Information) in which the delocalized/localized property is introduced in the radical cation state by two end-capping ferrocenes, thus mimicking the M–B–M structural formula. For comparisons, the same oligothiophenes-vinylene oligomers without ferrocenes are also studied (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Wenger et al designed and synthesized an organic mixed valence system using α,α′-bis­(diphenylamino) units as redox termini and studied the electronic coupling properties of oligothiophene derivatives. , Chen et al, Liu et al, , and Patra et al have reported bis­(ethynyl)­oligothiophene-bridged biruthenium complexes and investigated their electrochemical and spectroscopic properties in different redox states. The delocalized-to-localized charge transitions in thieno-vinylene oligomers with ferrocene as the redox active unit were studied using Raman spectroscopy. , Gidron and Bendikov reported that biferrocenyl-capped oligothiophenes offer slightly weaker electronic coupling than oligofurans. , Sato et al previously also reported mixed valence systems containing biferrocenyl-capped oligothiophenes, but without quantitative discussion on charge delocalization in such systems. , Despite the extensive work in the field, systematic studies on the influence of oligothiophenes of various chain lengths on the electronic delocalization in bimetallic mixed valence complexes [ML n (bridge)­ML n ] + are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The delocalized-to-localized charge transitions in thieno-vinylene oligomers with ferrocene as the redox active unit were studied using Raman spectroscopy. 22,23 Gidron and Bendikov reported that biferrocenyl-capped oligothiophenes offer slightly weaker electronic coupling than oligofurans. 24,25 Sato et al previously also reported mixed valence systems containing biferrocenyl-capped oligothiophenes, but without quantitative discussion on charge delocalization in such systems.…”
Section: ■ Introductionmentioning
confidence: 99%